The influence of language-biographical and language-ideological factors on the language use of bilingual speakers - Księżyk, Felicja (Papers in Linguistics, 2023)
There is now a consensus that bilinguals are not dual monolinguals, but that the languages they speak influence each other. The extent and shape of this influence is due, among other things, to differences in language-biographical and language-ideological aspects. The article refers to the results of research conducted as part of the German-Polish project Language across generations: contact induced change in morpho-syntax in German-Polish bilingual speech. Two different generations are interviewed in the project – early bilinguals in Poland (Generation Poland/GP) and late bilinguals in Germany (Generation Germany/ GD). In order to consider individual differences between the bilinguals, first of all only one of these speaker groups (GD) will be analysed. Then, the two language biographies which deviate from the phenomena induced by language contact will be analysed in more detail taking into account language-biographical differences to the GD as well as the internalised language ideologies.